Specification Study of Inter-State Ballistic Rockets in the Israeli-Palestinian war: A Review of Rockets used by Hamas, Hezbollah, and Taliban forces against Israel - Denda Wiguna; Toriq Furqon Al-Mujaddid; Yayat Ruyat; Heri Budi Wibowo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research analyzes the use of ballistic rockets by militant groups Hamas, Hezbollah and Taliban in the Israeli-Palestinian conflict. Through a literature review, this research examines the technical specifications of the rockets, their efficiency of use, and their economic and psychological impact on Israel. The findings show significant variations in the range and destructive capacity of rockets, as well as their effectiveness in asymmetric warfare strategies. The economic impact on Israel includes high costs for defense systems such as Iron Dome, damage to infrastructure, and disruption of economic activity. The research also discusses implications for the defense industry and the international arms trade. In conclusion, a comprehensive approach involving dialogue, economic development, and social reconciliation is needed to address the conflict, as well as further research in defense economics to develop more effective strategies.